Quantification of bacterial growth within orthopaedic scaffolds and assessment of the efficacy of antibacterial surface treatments - Zurawski, Michal (2022)
This thesis reports on the development of quantifiable methods for the assessment of bacterial bioburden within three-dimensional orthopaedic scaffolds, and the subsequent investigation of the effects of exposure of their surfaces to proteins has on the observed biofouling. The lack of readily available methods for this purpose, and the rising cost (both human and financial) of biofilm infection of orthopaedic devices prompted the need for this research. Existing methods are identified during the literature review, such as Confocal Laser Scanning Microscopy (CLSM) and Micro-CT which are used in the research field are first investigated for efficacy as they have been used in some studies. The aim of this study is to develop and validate a new analysis method to provide quantifiable, accurate and reliable results for the measurement of bacterial biofouling on flat and three-dimensional samples alike. This method is then used to measure the bacterial biofouling of samples once inoculated and incubated with S. aureus in a protein-rich environment they would be exposed to in situ inside a patient.